Time, the final frontier - Follain, Gautier; Dibus, Michal; Joshi, Omkar; Jacquemet, Guillaume (WILEY, 2025)
Cancer's notorious heterogeneity poses significant challenges, as each tumor comprises a unique ecosystem. While single-cell and spatial transcriptomics advancements have transformed our understanding of spatial diversity within tumors, the temporal dimension remains underexplored. Tumors are dynamic entities that continuously evolve and adapt, and relying solely on static snapshots obscures the intricate interplay between cancer cells and their microenvironment. Here, we advocate for integrating temporal dynamics into cancer research, emphasizing a fundamental shift from traditional endpoint experiments to data-driven, continuous approaches. This integration involves, for instance, the development of advanced live imaging techniques, innovative temporal omics methodologies, and novel computational tools.